The Precautions against Epidemics in Ottoman Islamic Media during Second Constitution Era - Tuna, Serhat Aras (ATATURK UNIV, FAC THEOLOGY, 2021)
Abstract Plague and cholera were the primary epidemics causing huge numbers of deaths until the 19th century. Similar to the rest of the world, Ottoman Empire was also affected by these two diseases periodically. Ottoman Empire could deal with them through quarantine regulations and by applying certain rules of hygiene, while also pursuing the developments of treatments and medication in Europe, at the same time. Epidemic diseases took place in Ottoman media widely, which was very important to inform the society and the governors. Even if there were attempts to control diseases through quarantine regulations, hadiths were also used as a religious base to support these regulations. As a result, the suggestions of modern medicine were supported by religious bases, and there were struggles against diseases financially and emotionally. In the final period of Ottoman Empire, the religious bases for struggling against diseases were hadiths, praying, and narratives. This study involves the pieces of writings related to diseases in Islamic periodicals which covered both religious and political issues. Extended Summary Throughout history, epidemic diseases have destroyed human beings and nature a lot. One of the oldest diseases causing huge devastation for humanity is plague. Also called as "taun", this disease's name was sometimes used to mean all the epidemic diseases, too. Especially in the Middle Ages, plague destroyed all the world and it caused some significant changes in demographical, political, financial and social issues. Plague was common in 19th century; however, in this period, there was also the epidemic of cholera. Both of these diseases were infectious and they were transmitted through germs. Although plagideas was the lack of well-developed medical ideas to fight against diseases. Microscopic devices to work on germs and the discovery of vaccines and medicine to control epidemics helped to re-define these diseases. One of the most effective ways to control the epidemics was keeping people in quarantine. The first modern quarantine in Ottoman Empire was in the period of Mahmud II (1808-1839). Quarantines were first implemented for the ships in trade centres and then they were used in all the places experiencing epidemics. However, Ottoman Empire and society had many difficulties in the implementation of quarantine, taking medicine and obeying medical instructions. Quarantine was seen as something "European" by some people, and it was seen as something not acceptable in Islam. As a result, some fatwas were given in that period so that people could obey the rules of quarantine. There were also a number of booklets published with the statement that quarantine was not forbidden by the religion, and the benefits of quarantine were explained in the official newspaper of the government, Takvim-i Vekayi. As a result, newspapers were used just after the first quarantine implementations so that they could be accepted by the society as they were the most common communication tools in that period. The governors and the literate people could get news about the developments through the country by reading newspapers and magazines. The most important ones of these publications were belonging to the groups with Pan-Islamic ideas. The Pan-Islamic ideology was supporting the idea of saving the religion from the superstitions and making Islamic rules as the base of the religion. The people supporting this ideology had both modernist and conservative ideas. One of the most important publications of the Pan-Islamist ideology was the magazine of Sirat-i Mustakim, known as Sebilurresad after a while. Apart from that, the publications such as Beyanulhak, Tearuf-i Muslimin and I'tisam also had Pan-Islamic views. These periodicals were publishing news and columns about many issues, especially the ones related to the Islamic World. One of these issues was the epidemics and the transmitting diseases. The aforementioned newspapers published a lot of pieces of information about the effects of plague and cholera. One of the reasons of these publications was the effort to persuade people to take precautions against these diseases; as a result, the reasons and the symptoms of these diseases were emphasized a lot. These periodicals mostly focused on the hygiene issues by using the Islamic rules of being clean in addition to the benefits of worshipping such as praying, fasting and going on a pilgrimage. The authors compared hygiene rules of Islam with European lifestyle and focused on the advantages of Islamic lifestyle. However, the main aim of the publications was to convince people about the necessity of modern medicine and quarantine. In that period, there were some ideas against the techniques used by the modern medicine. The primary precaution emphasized by Islamic publications was quarantine, which was being supported by the hadiths and religious narratives. The hadith most commonly used by the newspapers and the magazines was "If there is an illness somewhere, do not go there; if you are in somewhere with an illness, do not leave there." The hadiths like this were accepted to be about the quarantine which would help people to accept it. The authors were also suggesting the readers that they needed to obey the recommendations by the doctors within the framework of modern medicine. As a result, they tried to give the message that the religion protected the morale and the medicine provided the protection about the illnesses by giving some examples. In periodicals, there were also some prayers and religious stories such as the prayers of the Prophet Muhammad in order to relieve the ill people's minds.ue was observed in various places, cholera was known to have first appeared in India. These diseases generally occurred in the areas with hygiene problems and they were transmitted to other places through trade, wars and immigrations. There were some traditional methods to fight against the epidemic diseases in the Ottoman Empire, like in the other parts of the world. It became possible to work on the diseases in a more detailed way and to diagnose them in the 19th century with the developments in the industry of medicine and the technological developments. As a result, the fatalistic and submissive ideas about epidemics started to transform. The reason for having fatalistic
Keywords: History; Epidemics; Hadith; Quarantine; Plague; Ottoman